Molecular Diagnosis Is Vital to the Accurate Classification and Management of Thrombotic Thrombocytopenic Purpura in Children - Karsenty, Cecile L.; Kirk, Susan E.; Helber, Hannah L.; Esquilin, Jose M.; Despotovic, Jenny M.; Grimes, Amanda B. (Frontiers in Immunology, 2022)
Thrombotic thrombocytopenic purpura (TTP) is a rare but potentially life-threatening hematologic disease, presenting a myriad of diagnostic and management challenges in children. Here, we provide a review of this disorder and discuss 2 exemplary cases of TTP occurring in adolescents, emphasizing the need for consideration of late-onset congenital TTP (cTTP). We demonstrate the importance of early confirmation of ADAMTS13 enzyme deficiency and the presence or absence of ADAMTS13 inhibitor in order to rapidly initiate the appropriate life-saving therapies. Ultimately, molecular testing is paramount to distinguishing between congenital and acquired immune-mediated TTP.